CompTIA network+ N10-006 cert guide - Barker, Keith; Wallace, Kevin (Pearson IT certification, 2015)
This approved study guide helps you master topics on the CompTIA Network+ N10-006 exam, including the following: Computer network fundamentals The OSI model and TCP/IP stack Media types, infrastructure components, and network devices Ethernet technology IPv4 and IPv6 addresses Routing IP traffic with dynamic routing protocols DNAT, SNAT, and PAT Multicast routing Wide Area Networks (WANs) Wireless LANs Network optimization and QoS Windows and UNIX command-line tools for network administration and troubleshooting Network security Troubleshooting common Layer 2, Layer 3, and wireless networking issues CompTIA Network+ N10-006 Cert Guide contains proven study features that enable you to succeed on the exam the first time. Best-selling authors and expert instructors Keith Barker and Kevin Wallace share preparation hints and test-taking tips, helping you identify areas of weakness and improve both your conceptual knowledge and hands-on skills, essential for successful completion of the performance-based testing items on the exam. This complete, CompTIA-approved study package includes the following: A test-preparation routine proven to help you pass the exams approved by CompTIA Clearly defined chapter learning objectives covering all N10-006 exam topics Chapter-ending review questions and exam preparation exercises, which help you drill on key concepts you must know thoroughly The powerful Pearson IT Certification Practice Test software, complete with hundreds of well reviewed, exam-realistic questions, customization options, and detailed performance reports 40 performance-based practice question exercises to help you prepare for the hands-on exam questions An 80% discount off the Premium Edition eBook and Practice Test (a USD40 value!) A free copy of the CompTIA Network+ Simulator Lite software, complete with meaningful lab exercises that help you hone your hands-on skills More than 60 minutes of video mentoring from the author A final preparation chapter that guides you through tools and resources to help you craft your review and test-taking strategies An Exam Essentials appendix that quickly recaps all major chapter topics for easy reference, both in print and interactive digital format A key terms Glossary in both print and on the DVD, which acts as an interactive flash-card application Study plan suggestions and templates to help you organize and optimize your study time A 10% exam discount voucher (a USD27 value!) Well regarded for its level o...